Síntese, modelagem molecular e atividade antimicrobiana de complexos de Sb(III) e Bi(III) com ligantes derivados da 1,3,5-triazina e mesoiônicos do núcleo 1,3-tiazólio-5-tiolato - Martins, Evandro Paulo Soares (2016)
In this work the properties of the Sb(III) and Bi(III) complexes with mesoionic 1,3-thiazolium-5-thiolates and derivatives of the 1,3,5-triazine have been investigate from theoretical and experimental perspectives. This thesis was divided in three parts. In the first part, the performance of the semiempirical methods was assessed regarding to the prediction of the geometries of 54 Sb(III) complexes and 75 of Bi(III) with ligands, macrocyclic, heterocyclic, amine carboxylate tiocompounds and organometallic. The results indicated that AM1 and PM3 correctly predict the geometries of Sb complexes. PM6 is more accurate to predict the geometries of both Sb and Bi tiocompounds. However, PM6 presented an inability to reproduce the geometries of complexes with Sb−N bonds. In general, PM6 is more accurate to Bi complexes. In the second part, a theoretical and experimental study of Sb(III) and Bi(III) complexes with mesoionic 1,3-thiazólio-5-thiolates ligands has been performed. Five new complexes of formulas [Sb4Cl12(M1)3], [SbCl3(M2)]·H2O, [Bi4Cl12(M1)3], [Bi4Br12(M1)3] and [Bi4Br12(M2)3] have been synthesized and characterized by elemental analysis, IR, 13C NRM and conductivity measurements. Both complexes and mesoionic ligands were studied for their antimicrobial activity against species of bacteria Estafilococos aureus and fungi C. albicans, C. tropicalis, C. krusei. Sb complexes and their corresponding mesoionic ligands exhibited active against all the bacteria and fungi with minimum inhibitory concentration (MIC) in the range 256-1024 μg/mL. On the other hand, the Bi complexes not exhibit such activities. The theoretical study of the ground state geometries, electronic structures, thermodynamic stabilities and chemical bonds of the complexes [MX3(L)] (X = F, Cl, Br, L= M1, M2, M3) in gas phase have been carried out at DFT and MP2 theoretical level. Potential energy curves (PECs) were calculated using B3LYP, M06-2X and MP2 level of theory with 6-31G basis set for all element, except Sb and Bi which we applied the 6-31G(d) basis set coupled to relativistic pseudopotentials. The PECs calculated with MP2 and M06-2X indicated that the minima structures are stable by multiple intramolecular interactions. The analysis considering NBO charges indicated which the metal coordination led to the loss of mesoionic character, producing large charge delocalization in the ring. The analysis considering the frontier molecular orbitals calculated at M06-2X/cc-pVTZ pointed out a large contribution from atomic orbitals of the exocyclic sulfur and metal atoms to HOMO. However, the atomic orbitals of the metal did not contribute to LUMO, suggesting a process of charge transfer metal to ligand. QTAIM study of the complexes have pointed out that the metal-sulfur bonds are closed shell, with small degree of electron sharing. Besides, the QTAIM study has indicated the intramolecular interactions as hydrogen bonds, halogen bonds and metal-π interactions. In the final part of this thesis, we have been synthesized the complexes [SbCl3(TMT)], [Sb3Cl9(TMT)2], [Bi3Cl9(TMT)2], [Sb2Cl6(PIPT)]·4H2O, [Bi2Cl6(PIPT)]·2H2O and characterized them by elemental analysis, IR, 13C NRM and thermal analysis. Biological activities of both triazines and their complexes with Sb and Bi against bacteria E. aureus and fungi C. albicans, C. tropicalis, C. krusei have been obtained. Sb complexes exhibited activities against all bacteria and fungi with CIM ranging in the interval of 512-1024 μg/mL. Both triazine ligands and their bismuth compounds did not exhibit such activities.